RELATIONSHIP OF THE PROTON FLUX INTENSITY WITH RELATIVE DISTANCE BETWEEN HARMONICS OF TYPE II RADIO BURSTS IN THE RANGE 25-180 МHZ - Isaeva, E. A. (Одеські астрономічні публікації, 2019)
In this work, the relative distance be- tween the harmonics of type II radio bursts and its rela- tionship with the intensity of the proton flux with an ener- gy > 30 MeV are studied. The studied sample contains 112 solar proton events (SPE) for the period from 24-11-2000 to 20-12-2014 years, accom- panied by type II radio bursts in the range of 25-180 MHz. For analysis, we used the original recordings of the dy- namic spectrum in the range of 25-180 MHz from the So- lar Radio spectrograph (SRS), as well as the original re- cordings of the proton flux intensity with an energy > 1- 100 MeV according to GOES data. A comparative analysis showed that for the vast majori- ty of solar proton events, the relative distance between the harmonics of a type II burst varies over time over a wide range. Moreover, each event is characterized by a gradual decrease in the relative distance to the minimum value with subsequent increase. In this work, we also studied the relationship between the proton flux intensity of solar cosmic rays (SCR) and the relative distance between the harmonics of type II ra- dio bursts at a given time. A comparative analysis showed that there is a fairly strong relationship between the proton flux intensity with an energy > 30 MeV and the frequency f 1 at the fundamental harmonic, at which the minimum value of the relative distance between the harmonics of the type II burst is observed. It was shown that the lower the frequency f 1 at the fundamental harmonic, the higher the intensity of the proton flux.